A gestão da informação e do conhecimento no âmbito da transformação digital por análise bibliométrica - Cavaretti, Nicholas (2023)
With the evolution, intermediary and convergence of digital, biological and physical technologies, the scenario of the Fourth Industrial Revolution is directly associated with the conceptions of the next steps of Digital Transformation and the concept of Industry 4.0. In this way, it is noted that Information Science could have the opportunity to enhance better results or approaches in the digital scenario. In this sense, this research aims to evolve, understand and approach the relationships between the topics Information Management, Knowledge Management and Digital Transformation, through bibliometric analysis. Indeed, it is classified research of a basic nature and with a quantitative-qualitative and exploratory-descriptive approach. The choice of the Web of Science database made it possible to recover, by descriptors, 5,615 records for Information Management, 5,297 records for the term Digital Transformation and, for the term Knowledge Management, 9,924 records. For data processing, visualization and construction of maps and networks, the VOSViewer tool and also Excel were used. Data such as: the collaboration network between countries, the evolution of publications and the co-occurrence of keywords through maps were analyzed and presented. Thus, 24 concepts were obtained that can be considered the connections that support Information Management and Knowledge Management in the context of Digital Transformation. It was found that there is a convergence that approaches the themes through Computer Science, Business and Economics (Business Economics), Engineering and Information Science when directed and focused on the identified research areas and under analysis to the most productive countries, in the Within the scope of research focused on Knowledge Management and Information Management publications, it is possible to verify that the first three positions in both rankings remain, being China United States and England. On the other hand, it can be considered that Germany, as a precursor of Digital Transformation initiatives, remains the leader in the ranking of publications on the subject. It is suggested as future studies the use of other metrics for analysis and measurement of results, as well as the use of other indexing bases of scientific documents and software for bibliometric analysis.